(untitled) (Bioscience Journal, 2016)
The objective of this study was to analyze the contribution, of the inclusion of the subject of Geriatric Dentistry in the academic curriculum of a dentistry graduation course, to the understanding and attitudes of undergraduates in the care of the elderly. A total of 59 final-year students enrolled in two dental faculties took part in the study: GD Group - where Geriatric Dentistry was included in the curriculum (n=21; 75% of the total) and the NGD Group - where it was not (n=38; 77.5% of the total). The data were obtained by means of a questionnaire completed anonymously by the students, taking into account the following aspects: content and knowledge of geriatric dentistry and professional expectations. The principal source of knowledge of Geriatric Dentistry for both groups was the graduation course, with oral healthcare for the elderly being covered in other areas of study for 79% of the respondents in the NGD Group and 61.9% in the GD Group. Amongst the NGD Group, 5.3% looked for information on the topic outside the faculty, as opposed to the GD Group where no such actions were reported. When questioned as to whether they felt sufficiently prepared to provide elderly clinical care, the frequency of responses related to insecurity was greater in the GD Group. The inclusion of Geriatric Dentistry as a subject in the university curriculum had some positive aspects on students’ knowledge, and made them more aware of the importance of adequate professional preparation for caring for elderly patients, reflected in the lack of security identified with regard to the complexities of caring for people in this age group.